A volcano wakes up - Mitchell, Julie (Pearson Education Harlow, Essex, 2012)
A Volcano Wakes Up by Julie Pringle vividly portrays the dramatic awakening of a volcano through poetry, capturing its power and impact on the surrounding environment.